2017
DOI: 10.18632/oncotarget.14699
|View full text |Cite
|
Sign up to set email alerts
|

A new model of multi-visceral and bone metastatic prostate cancer with perivascular niche targeting by a novel endothelial specific adenoviral vector

Abstract: While modern therapies for metastatic prostate cancer (PCa) have improved survival they are associated with an increasingly prevalent entity, aggressive variant PCa (AVPCa), lacking androgen receptor (AR) expression, enriched for cancer stem cells (CSCs), and evidencing epithelial-mesenchymal plasticity with a varying extent of neuroendocrine transdifferentiation. Parallel work revealed that endothelial cells (ECs) create a perivascular CSC niche mediated by juxtacrine and membrane tethered signaling. There is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…We noticed that 3-kb upstream promoter of ROBO4 contains information for endothelial cell typespecific expression in the intact endothelium; 46 this observation was confirmed by our published proteome data, which suggest that LSECs have highest ROBO4 abundance in murine liver, 47 and endothelial cell-specific adenovirus was also created based on this demonstration. 39 Furthermore, RGD, which is considered an endothelial cellspecific polypeptide, 48 was used to modify these adenoviruses and PEG particles carried with honokiol, ensuring the endothelial cell specificity of adenovirus and nanoparticle. Moreover, adenovirus had higher gene transfer efficiency than lentivirus and more space to assemble LSEC-specific elements than recombinant adeno-associated virus (rAAV) to ensure the high LSEC targeting, which may act as a more effective vector involved in anti-fibrotic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We noticed that 3-kb upstream promoter of ROBO4 contains information for endothelial cell typespecific expression in the intact endothelium; 46 this observation was confirmed by our published proteome data, which suggest that LSECs have highest ROBO4 abundance in murine liver, 47 and endothelial cell-specific adenovirus was also created based on this demonstration. 39 Furthermore, RGD, which is considered an endothelial cellspecific polypeptide, 48 was used to modify these adenoviruses and PEG particles carried with honokiol, ensuring the endothelial cell specificity of adenovirus and nanoparticle. Moreover, adenovirus had higher gene transfer efficiency than lentivirus and more space to assemble LSEC-specific elements than recombinant adeno-associated virus (rAAV) to ensure the high LSEC targeting, which may act as a more effective vector involved in anti-fibrotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid any nonspecific effects of chemical Erk1/2 and Akt agonists and inhibitors, we used arginylglycylaspartic acid-roundabout guidance receptor 4 (RGD-ROBO4) modified adenovirus to separately express constitutively active mitogen-activated protein kinase (MEK)1 (Ad-CA MEK1) and dominant-negative Akt (Ad-DN Akt), which are specific for endothelial cells, 39,40 to investigate the role of Erk1/2 and Akt activity in LSECs during chronic liver injury. Most of the Ad-RGD-ROBO4 vectors were located in the liver sinusoidal endothelium (Figure S5A).…”
Section: The Erk1/2-akt Axis In Lsecs Was Required For Liver Regeneration and Fibrosis Balance In Vivomentioning
confidence: 99%
“…For example, a study has shown that DKK1 expression increases early in prostate cancer development and decreases during progression from primary tumor to metastasis, which would indicate the activation of the Wnt pathway [190]. Additionally, a recent study presented a new model of multi-visceral and bone metastatic prostate cancer with activation of Notch and Wnt pathways [191] adding to the complexity of Wnt signaling in contribution to a metastatic process in prostate cancer.…”
Section: Prostate Cancer Liver Metastasismentioning
confidence: 99%
“…Sectioning of frozen organs was carried out using the CryoJane Taping System (Leica Biosystems Inc). All frozen section slides were subject to immunofluorescence staining analysis in accordance with the standard techniques (8). Primary antibodies used in this study included hamster anti-CD31 (EMD Millipore), rat anti-endomucin (eBioscience), rat anti-PDGFRb (eBioscience), rabbit anti-HSVtk (Dr. Summers's laboratory), and Alexa Fluor 488 or 594-conjugated secondary antibodies (Jackson ImmunoResearch Laboratories).…”
Section: Tissue Harvest and Immunofluorescence Stainingmentioning
confidence: 99%
“…Triple-immunodeficient NSG mice allow for modeling of all metastatic sites as published previously (8,9). For systemic metastases, mice were injected intracardially with 5 Â 10 5 786-0 renal carcinoma cells (Luciferase gene expressed).…”
Section: Animal Studies For Therapeutic Index Gainsmentioning
confidence: 99%